GAMBARAN MANAJEMEN LIMBAH ARSIP PADAT PADA FASILITAS PELAYANAN RAWAT JALAN DI PUSKESMAS KARANG TALIWANG KOTA MATARAM TAHUN 2024 - Zaori, Sopian; Slamet Mardiyanto Rahayu; Fathurrahman; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2024)
Based on the results of research at the Karang Taliwang Community Health Center, the solid medical waste management process goes through several stages, namely starting from selecting and storing medical waste according to the type in each room at the Karang Taliwang Community Health Center, transporting solid medical waste to a temporary shelter is carried out every day after working hours, then the collection or temporary storage is in a warehouse within the community health center which is located far from the reach of the public so that it does not endanger the people who visit, for the final stage, namely disposal to the final location which will be carried out by parties who collaborate with the Community Health Center. from PT Artama Sentosa who came to the Health Center to transport them to the final management site. The results of the research show that the management of medical solid waste at community health centers has met the standards according to the Regulation of the Minister of Health of the Republic of Indonesia Number 18 of 2020 Management of Medical Waste for Regional-Based Health Service Facilities.